Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1162/rest_a_00759
|View full text |Cite
|
Sign up to set email alerts
|

Inference in Differences-in-Differences with Few Treated Groups and Heteroskedasticity

Abstract: Differences-in-Differences (DID) is one of the most widely used identification strategies in applied economics. However, inference in DID models when there are few treated groups is still an open question. We show that usual inference methods used in DID models might not perform well when there are few treated groups and residuals are heteroskedastic. In particular, when there is variation in the number of observations per group, we show that inference methods designed to work when there are few treated groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
160
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(161 citation statements)
references
References 32 publications
(74 reference statements)
0
160
1
Order By: Relevance
“…When there are only a few available clusters, one should look for alternative procedures, see e.g. Conley and Taber (2011) and Ferman and Pinto (2018).…”
Section: Asymptotic Theory For Summary Parametersmentioning
confidence: 99%
“…When there are only a few available clusters, one should look for alternative procedures, see e.g. Conley and Taber (2011) and Ferman and Pinto (2018).…”
Section: Asymptotic Theory For Summary Parametersmentioning
confidence: 99%
“…In this subsection, I examine the sensitivity of the results by running different specifications of the synthetic control method. Recently, Ferman and Pinto () have shown that asymptotic bias can exist in the synthetic control estimator when a subset of common factors is nonstationary. In this case, even a close‐to‐perfect pretreatment match for a long set of preintervention periods (which I attain when applying the synthetic control method) does not guarantee that the asymptotic bias becomes zero.…”
Section: Local Effects From the Research Universitymentioning
confidence: 99%
“…I also separately examine the employment of highly skilled subsectors in service industries, and find that the campus opening also increases the employment in highly skilled sectors. These findings are robust even when I detrend the outcome variables as suggested by Ferman and Pinto () or control for local industrial compositions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A third major difference is that our procedure works in conjunction with many modern high-dimensional esti-mators, whereas Andrews (2003) focuses on low-dimensional GMM-type models. Hahn and Shi (2016, Section 5) informally suggest applying the end-of-sample stability test in the context of synthetic control methods and Ferman and Pinto (2017a) use a version of this test in the context of difference-in-differences approaches with few treated groups.…”
Section: Related Literaturementioning
confidence: 99%